Fractional-Order Based Control Strategies for Essential Oil Extraction Process - Tajjudin, Mazidah; Nor Syafikah Pezol; Siti Nur Hasinah Johari; Haslizamri Md Shariff; Mohd Hezri Fazalul Rahiman (International Journal of Integrated Engineering, 2024)
Essential oil extraction through steam distillation is widely recognized as a preferred technique in the industry due to its practicality and cost-effectiveness. Despite its advantages, the high process temperatures associated with distillation can lead to the formation of unwanted chemical compositions in the essential oils. To address this challenge, significant research has been directed towards developing advanced control techniques to enhance the extraction process by means of regulating the operational temperature. Traditional PID controllers are often used, but it has limitations, prompting to the exploration of more sophisticated methods such as advanced PID, Fuzzy-based controller, and Model Predictive Control (MPC). This paper delves into the potential of various fractional-order based controllers, including fractional-order PID (FOPID), Internal Model PID Controller with Fractional-order filter (IMC-PID FOF), and CRONE towards improving the control performance. Evaluations based on output response, control signal behaviours in response to step inputs, setpoint changes, and disturbance tests indicate that IMC-PID-FOF achieves the best control performance across all test conditions, followed by CRONE-2 and FOPID. The yield from C. nardus extracted under controlled steam temperature at 85°C had shown some alterations from the uncontrolled condition in terms of colour, refractive index and major chemical compounds. However, the composition is greater than the range stipulated by the standard ISO 3849:2003.